Prognostic value of beta-blocker doses in patients with ventricular tachyarrhythmias - Schupp, Tobias; Ziyadova, Sevil; Reinhardt, Julius; Sag, Yusuf Ugur; Zworowsky, Max von; Reiser, Linda; Abumayyaleh, Mohammad S. A.; Weidner, Kathrin; Saleh, Ahmad; Mashayekhi, Kambis; Bertsch, Thomas; Abba, Mohammed L.; et al. (Heart and vessels, 2022)
The study investigates the prognostic significance of beta-blocker (BB) dose in patients with ventricular tachyarrhythmias. Limited data regarding the prognostic impact of BB dose in ventricular tachyarrhythmias is available. A large retrospective registry was used including consecutive patients on BB treatment with episodes of ventricular tachycardia (VT) or fibrillation (VF) from 2002 to 2015. Discharge BB doses were grouped as > 0-12.5%, > 12.5-25%, > 25-50%, and > 50% according to doses used in randomized trials. The primary endpoint was all-cause mortality at three years. Secondary endpoints comprised of a composite arrhythmic endpoint (i.e., recurrences of ventricular tachyarrhythmias and appropriate ICD therapies) and cardiac rehospitalization. Kaplan-Meier survival curves and multivariable Cox regression analyses were applied for statistics. A total of 1313 patients with BB were included; most patients were discharged with > 25-50% of BB target dose (59%). At three years, > 12.5-25% of BB target dose was associated with improved long-term mortality as compared to the > 0-12.5% group (HR = 0.489; 95% CI 0.297-0.806; p = 0.005), whereas higher BB doses did not improve survival (> 25-50%: HR = 0.849; p = 0.434; > 50%: HR = 0.735; p = 0.285). In contrast, the composite endpoint and risk of rehospitalization were not affected by BB target dose. In conclusion, > 12.5-25% of BB target dose is associated with best long-term survival among patients with ventricular tachyarrhythmias. In contrast, risk of the composite arrhythmic endpoint and risk of cardiac rehospitalization were not affected by BB dose.
Gesehen am 19.12.2023